Soft x-ray laser interferometry of dense plasmas - Filevich, Jorge, author; Rocca, Jorge J. G., advisor (Colorado State University. Libraries, 2007)
This Dissertation presents the results of the study of plasmas using soft x-ray laser interferometry. The use of soft x-ray wavelengths (14.7 nm and 46.9 nm) permits probing plasmas that are denser and that have steeper density gradients than those that can be probed using optical interferometry. The use of diffraction gratings as beam splitters permitted the construction of a novel interferometer design that is robust, stable and with high throughput. The measurements conducted include the first demonstration of soft x-ray laser interferometry with picosecond resolution. The first set of results presented herein are the observation of an unexpected on-axis density depression in narrow-focus laser-created plasmas. It is caused by plasma-radiation-induced ablation of target material outside of the region irradiated by the plasma-heating laser. This colder material expands at a slower velocity than the hotter central region, resulting in the observed on-axis density depression. The effect is shown to be a general phenomenon, present in many narrow focus plasmas under different irradiation conditions. The second set of results unveiled the significant contribution of bound electrons to the index of refraction of multiply ionized plasmas. Experiments that mapped the density of aluminum plasmas using a λ=14.7 nm laser beam showed interference fringes that bent in the direction opposite to that expected, contradicting the widely accepted assumption that the index of refraction for multiply ionized plasmas at soft x-ray wavelengths only depends on the free electrons. The contribution of bound electrons to the index of refraction is shown to be significant, and to affect a broad range of wavelengths due to numerous bound-bound and bound-free transitions present in the plasma. Moreover, the contribution of bound electrons to the index of refraction was shown to be important in several materials at different probe soft x-ray wavelengths, in particular for tin, silver and carbon plasmas probed at λ=46.9 nm. This fundamental result affects not only the interpretation of soft x-ray interferograms for plasma density measurements, but also the propagation of soft x-ray light in plasmas in general.
Keywords: anomalous index refraction; bound electrons; plasma diagnostics; plasma interferometry; x-ray laser; fluid dynamics; gases; plasma physics